2008
DOI: 10.2174/138920108783497659
|View full text |Cite
|
Sign up to set email alerts
|

Joint Diseases and Matrix Metalloproteinases: A Role for MMP-13

Abstract: The role of matrix metalloproteinases in disease has been investigated over the last two decades. A focus on this family of proteases is particularly emphasized in two major arthritides in humans, osteoarthritis and rheumatoid arthritis. Early work described the presence of multiple MMP family members in the joint of the disease state and recent advances in the development of new knockout mice and disease models have allowed investigators to directly test the role of the MMP proteases in arthritis. MMP-13 is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
212
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(218 citation statements)
references
References 56 publications
6
212
0
Order By: Relevance
“…The MMP‐13 knockout (KO) mice on a 129/Sv genetic background were generated by microinjection of embryonic stem cells into C57BL/6J blastocytes as described before 30, 31. Adult MMP‐13 KO mice were back‐crossed with C57BL/6J strain for at least five times.…”
Section: Methodsmentioning
confidence: 99%
“…The MMP‐13 knockout (KO) mice on a 129/Sv genetic background were generated by microinjection of embryonic stem cells into C57BL/6J blastocytes as described before 30, 31. Adult MMP‐13 KO mice were back‐crossed with C57BL/6J strain for at least five times.…”
Section: Methodsmentioning
confidence: 99%
“…MMP-13 is expressed by chondrocytes and synovial cells in human OA and RA and is thought to play a critical role in cartilage destruction. The recent development of a MMP-13 knockout mouse has documented the important role played by this enzyme in cartilage formation and further studies under pathological conditions should reveal the function of this enzyme in the progress of the disease (Takaishi et al, 2008) (see Table 6). Several in vitro studies have demonstrated the importance of MMP-13 in human arthritis (Bau et al, 2002;Billinghurst et al, 1997;Mitchell et al, 1996;Reboul et al, 1996).…”
Section: Neoplastic Diseasesmentioning
confidence: 99%
“…According to Kojima, Hoso, Watanabe, Matsuzaki, Hibino, Sasaki 46 , these changes may be related to the presence of flocculation, corrosion and cracks in the articular cartilage. Taking into consideration the findings of studies by Hadler-Olsen, Fadnes, Sylte, Uhlin-Hansen, Winberg 47 and Takaishi, Kimura, Dalah, Okada, D'Armiento 48 , the changes that were observed in the present study in the LG and EG may have been the result of an increase in the rate of synthesis and the secretion of matrix-degrading enzymes by chondrocytes, as well as the production of metalloproteases that are capable of unfolding collagen and proteoglycans, which release their fragments in the articular fluid, thereby weakening the cartilage matrix. Synovial fluid and the fibrous articular capsule respond to these fragments and other biochemical mediators, such as cytokines and leukotrienes, which leads to changes in the other components of the joint.…”
Section: Discussionmentioning
confidence: 99%